Pendidikan Anak: Perspektif Abdullah Nashih ’Ulwan - Azis Abdullah; Anisa Nur Hidayah (Jurnal Al-Manar, 2023)
Abdullah Nasih'ulwan is a scholar, da'i who creates books on education. According to Abdullah Nashih'ulwan every child has a different character as well as intelligence, abilities and emotions. In this case, Abdullah Nashih'ulwan describes several educational materials that can be used by educators, namely faith education, moral education, physical education, cognitive education, psychological education, social education and sexual education. Several methods in educating children are: exemplary method, habit method, advice method, attention and supervision method and punishment method.Keywords: concept, education, children's education.